SMART INFORMATION SYSTEMS FOR THE MANAGEMENT OF INNOVATIONS TO RAISE THE QUALITY OF DIGITAL BUSINESS PRODUCTS - Aiman M. Abdikarimova; Aiperi K. Kurmanbekova; Malakhatkan S. Ysakova; Marina A. Sanovich; Tatevik G. Vardanyan (Proceedings on Engineering Sciences)
This paper presents an analysis of the capabilities of the selected sectors of the economy to implement innovations that are based on smart information systems, which are used for the improvement of product quality. We studied the implementation of these information systems in the innovative development of trucks in the EU and the energy sector in developed and developing countries. We proved the offered research hypothesis regarding the connection between the implementation of innovations that are aimed at an increase in digital products’ quality and the development of smart information systems. We demonstrated that the achievement of a wide range of positive advantages due to the implementation of smart information systems in the form of various digital solutions involves the necessity of ensuring reliable financing. It can be implemented with the use of new approaches to the assessment of reliability and creditworthiness of borrowers (companies working in the IT sphere). The objective of this paper was to determine and describe the possibilities of using smart information systems in the management of innovations that are aimed at ensuring the improvement of the quality of digital business products. We used the system approach, statistical method, and trend method in this research. Its scientific novelty lies in the identification of the possibilities of implementing smart information systems in the management of innovative growth in the context of improvement of the indicators of digital business products’ quality.